Top of Central Switzerland = Zeitgenössische Kunst aus der Zentralschweiz - Banz, Stefan; Christen, Gabriela; Fischer, Peter; Imfeld, Al; Lichtin, Christoph; Neubauer, Susanne; Porter, Allan; Stadler, Hilar; Vittali, Peter (Luzern : Kunstmuseum Luzern, 2007)
Albert, Judith ; Bachmann, Carolyn ; Banz, Stefan ; Baselgia, Guido ; Bissig, Nathalie ; Blätller, Rudolf ; Brefin, Daniel ; Bucher, Patricia ; Dias, Mauricio ; Dillier, Monika ; Döbeli, Markus ; Egloff, Anton ; Estermann, Robert ; Fähndrich, Walter ; Fries, Pia ; Galic, Goran ; Gritsch, Stefan ; Günther, Monika ; Ineichen, Irma ; Kathriner, Christian ; Kistler, Hans-Peter ; Lenzlinger, Jörg ; Lichtsteiner, Alois ; Lüthi, Urs ; Markowitsch, Rémy ; Marusic, Tatjana ; Naegelin, Barbara ; Nager, Bessie ; Nedeljkovic, Sladjan ; Nova, Nils ; Odermatt, Alexander ; Odermatt, Josef Maria ; Regli, Peter ; Reto Gredig, Gian ; Riedweg, Walter ; Rohner, Patrick ; Rondinone, Ugo ; Rütimann, Christoph ; Sandoz, Claude ; Schill, Ruedi ; Schnider, Albrecht ; Schwander, Markus ; Sperini, Loredana ; Spielhofer, Hildegard ; Steiner, Gerda ; Stobbe, Peter ; Strba, Annelies ; Streuli, Beat ; Vittali, Peter ; Wanner, Franz ; Winnewisser, Rolf ; Wyrsch, Charles ; Zanni, Margot ; Zurfluh, Christine ; Zwimpfer, Eva
biog. p. 151-153
Duits
Exhibition. Top of Central Switzerland = Zeitgenössische Kunst aus der Zentralschweiz. Kunstmuseum Luzern, 15.12.2007 - 17.02.2008.
boek
Keywords: Zwitserland